ANALYSIS OF FACTORS AFFECTING PRACTICE INCOME SMOOTHING (INCOME SMOOTHING) ON BANKING INSTITUTIONS LISTED IN STOCK EXCHANGE INDONESIA - Wulansari, Desy; one, Dr. Prihantoro; one, Dr. Masodah (Accounting, 2009)
This research was conducted to identify the banking institution who practice income smoothing in the go-public company in Indonesia Stock Exchange. Of the 29 companies that successfully used as a sample of 25 companies without involving the companies that make acquisitions and merger also does not publish financial statements in the period of study. With Eckel index proved to have banking institutions who practice income smoothing, From the results obtained there are 20 companies doing income smoothing and 5 companies that do not practice income smoothing. Identification was also conducted to determine the factors that affect the practice of income smoothing. This is done because the inconsistency of previous studies. Through regression test was found among the three variables (company size, profitability and operating leverage) no significant influence on income smoothing. The inconsistency of research results may occur due to different samples, the period of the study and the number of samples used. Other factors also affect this income smoothing evidenced from the results of R2 (R Square) in the model summary table at 1.5%, which means from three independent variables affect only 1.5% of income smoothing while 98.5% are influenced by variables other. Keywords : income smoothing, banking institutions